Characterization and gravimetric analysis of the dissolved quartz in the conversion of coal fly ash to sodalite - Mohamed, Mohd. Hilmi (2012)
Coal fly ash (CFA) is a waste product produced from the electrical power plant and hazardous towards the environment. However, the high composition of silica and alumina in the CFA makes it useful as raw materials in the zeolite synthesis. However, the presence of silica in the form of quartz in the CFA does not facilitate the transformation of CFA to zeolite at 100oC and autogeneous pressure. In this study, CFA was converted to zeolites in various NaOH concentrations by microwave heating at various heating time. All synthesized product were characterized by X-ray diffraction(XRD), and gravimetric analysis. XRD has shown that quite pure sodalite in nanosize has been formed as early as 15 minutes and increase with time. Prolong heating up to 45 minutes has reduced the content of quartz to ca 20%. Gravimetric analysis performed on the liquor of the reaction showed that the dissolved silica decrease with increase of heating time indicating that most of the dissolved quartz is used up to form sodalite framework. Hence, quartz of CFA did help in enhancing the crystallinity of the formed sodalite after prolong heating.